CRYPTOSPORIDIOSIS IN PEDIATRIC PATIENTS - Nélida SAREDI; Javier BAVA (Revista do Instituto de Medicina Tropical de São Paulo, 1998)
Cryptosporidium was detected in 21 (3.8%) individual stool samples collected from 553 pediatric patients hospitalized in our center employing a Telemann concentration technique (formalinethercentrifugation) and stained with the modified Kinyoun method. The mean age of populations with Cryptosporidiosis (16 boys and 5 girls) was 11 months; 15 months for girls and 6.5 for boys. Ages of 81% of them were less than 19 months. Seventysix per cent of patients lived on the outskirts of Buenos Aires and 71% lacked pretreated running water at home. In 62% of the cases parasitological diagnoses coincided with warm seasons. At diagnosis mucous (63%) or watery (36%) diarrhea was presented in 90% of the patients with a median of 5 (38) bowel movements per day. Fever was presented in 66% of patients while abdominal pain and vomits in 60% and 52%, respectively. The median time from hospitalization up to parasitologic diagnosis was 20 days. Concomitant diseases observed were malnutrition, acute leukemia, bronchiolitis, HIV infection, anemia, celiac disease, myelofibrosis, vitelline sac tumor, neutropenia, osteosarcoma and dehydration. Cryptosporidiosis in our environment seems to occur more frequently in children younger than 18 months of age; who present diarrhea; are immunodeficient; come from a low socioeconomical background; and who live in poor sanitary conditions with no potable running water. Criptosporidiose em pacientes pediátricos Cryptosporidium foi detectado em 21 (3,8%) amostras de fezes obtidas de 553 pacientes pediátricos atendidos em nosso centro médico, com a técnica de concentração de Telemann (formalinaétercentrifugação) e coloração de Kinyoun modificada. A média etária da população com criptosporidiose (16 meninos e 5 meninas) foi de 11 meses: 15 para as meninas e 6,5 meses para os meninos; 81% das idades desses pacientes foram menores de 19 meses; 76% eram moradores nas zonas marginais de Buenos Aires e 71% com falta de água potável. Em 62% dos casos os diagnósticos parasitológicos foram efetuados nas ...